The Management of Meaning – Conditions for Perception of Values in a Hierarchical Organization - Kirkhaug, Rudi (Journal of business ethics, 2008)
This article argues that the introduction of value based management in a decentralized, hierarchical, and rule-based organization will add to existing informal and formal systems instead of replacing them. Consequently, employees’ perception of and willingness to embrace and operationalize centrally imposed values were assumed to be dependent upon existing emotional, social, and formal processes and structures. Hierarchical regression analysis on data from a maritime company (N = 408) gathered in Norway in 2004 – which claims to be a learning and value based company – showed that affective commitment and group coherence correlated positively with perception of values among employees. Formalization was positively but insignificantly correlated, whereas loyalty toward immediate superiors was significantly negatively correlated with perception of values.